Malaria Incidence Trends and Their Association with Climatic Variables in East Kalimantan, Indonesia, 2014–2020 - Muhammad Rasyid Ridha; Liestiana Indriyati; Juhairiyah Juhairiyah; Harninda Kusumaningtyas (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Malaria is still a worldwide health problem, which includes Indonesia. Vector-borne diseases are climate-sensitive and this has raised extended concern over the implications of global climate change on future disease risk. This study aims to analyze the relationship between climate factors and malaria cases in East Kalimantan Province as an illustration to assist the malaria elimination program. Methods: Laboratory confirmation of malaria cases 2014-2020 was analyzed for trends derived from the E-Sismal data. Decomposition analysis was performed to assess seasonality. Climatic data (humidity, temperature, and rainfall) were analyzed with the incidence of malaria using Spearman rank correlation and model analysis with Poisson regression. Results and Discussion: The API value did not decrease significantly, which was only 0.07% from 2014 to 2020, but there was a change in the number based on the type of parasite from Plasmodium falciparum to vivax, which means that program intervention efforts have occurred, while Plasmodium vivax can relapse. There was a seasonal trend decomposition of monthly Plasmodium falciparum and Plasmodium vivax from December to March. Relative humidity shows a positive correlation while monthly temperature shows a negative correlation with P. vivax malaria cases each month. Conclusion: The outputs from this study are going to be useful at numerous levels of decision-making, for example, in fitting associate early warning and property methods for temperature change and climate change adaptation for malaria infection management programs in East Kalimantan.